Realist evaluation of a theory-based life skills programme aiming to prevent addictive behaviours in adolescents: the ERIEAS study protocol. Issue 6 (29th June 2020) - Martin-Fernandez, Judith; Affret, Aurelie; Martel, Emma; Gallard, Romain; Merchadou, Laurence; Moinot, Laetitia; Termote, Monique; Dejarnac, Vincent; Alla, François; Cambon, Linda
Abstract : Introduction: Adolescence is a sensitive life stage during which tobacco, alcohol and cannabis are used as ways to learn and adopt roles. There is a great deal of interest in substance use (SU) prevention programmes for young people that work to change representations of these products and help with mobilisation of life skills. Unfortunately, few existing programmes are evidence-based. In France, a programme called Expériences Animées (EA, Animated Experiences) has been developed, inspired by life skills development programmes that have been proven to be successful. The EA programme uses animated short movies and talks with high school and secondary school pupils about the use of psychoactive substances and addictions. By allowing life skills mobilisation and modifying representations and beliefs about SU, it is aimed at delaying initiation of use of psychoactive substances, preventing adolescents from becoming regular consumers, reducing the risks and harms related to the use of these substances and opening the way for adapted support measures. We are interested in understanding how, under what circumstances, through which mechanisms and among which adolescents the EA programme works. Therefore, we have developed the ERIEAS study ('Evaluation Réaliste de l'Intervention Expériences Animées en milieu Scolaire'; Realist Evaluation of the EA Intervention in Schools). Methods and analysis: EA will be conducted in 10 schools. A multi-case approach will be adopted with the aim of developing and adjusting an intervention theory. The study comes under the theory-driven evaluation framework. The investigation methodology will include four stages: (i) elaboration of a middle-range theory; (ii) data collection for validating/adjusting the theory; (iii) data analysis; and (iv) refinement and adjustment of the middle-range theory and definition of the programme's key functions. Ethics and dissemination: The study will provide evidence-based results to health authorities to help in the rollout of health promotion strategies in schools. It will provide knowledge about the strategic configurations most suitable for leading to life skills mobilisation and change young people's representations about SU. The project will be carried out with full respect of current relevant legislation (eg, the Charter of Fundamental Rights of the European Union) and international conventions (eg, Helsinki Declaration). It follows the relevant French legislation of the research category on interventional research protocol involving the human person. The protocol was approved by the Comité et Protection des Personnes (CPP), that is, Committee for the Protection of Persons CPP SUD-EST VI n°: AU 1525 and was reported to the Agence Française de Sécurité Sanitaire des Produits de Santé (ANSM) that is, the French National Agency for the Safety of Health Products. It is in conformity with reference methodology MR003 of Bordeaux University Hospital (CNIL n° 2 026 779 v0). Trial registration details This research has been registered on ClinicalTrials.gov (No. NCT04110626 ). The research project is registered in the European database ID-RCB (No. 2019-A01003-54).